2007
DOI: 10.1097/01.aids.0000279708.09180.f5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment acceleration program and the experience of the DREAM program in prevention of mother-to-child transmission of HIV

Abstract: The DREAM HIV-1 PMTCT protocol was safe and efficacious in reducing transmission in infants of 1 and 6 months of age. Results were comparable to those from developed countries. Breastfeeding among HIV-1 infected mothers receiving HAART posed no additional risk of late postnatal HIV-1 transmission to the infant by 6 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 29 publications
4
117
1
1
Order By: Relevance
“…Although there is growing evidence that people with HIV get reinfected and or super-infection with another 'strain' of HIV, including drug-resistant strains (10), this is thought not to be of major public health significance (3,11). There is also increased chance that those who become pregnant are likely to transmit the HIV by mother to child transmission (MTCT) (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is growing evidence that people with HIV get reinfected and or super-infection with another 'strain' of HIV, including drug-resistant strains (10), this is thought not to be of major public health significance (3,11). There is also increased chance that those who become pregnant are likely to transmit the HIV by mother to child transmission (MTCT) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover ART by diminishing the viral load in an individual on treatment greatly decreases the probability of sexual as well as mother to child transmission of HIV (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although exclusive breast feeding was advised, only 47.06% mothers exclusively breastfed the babies, which is less compared to Prameela et al 9 23 showed a transmission rate of <2% with alternatives to breast feeding without an increase in mortality in non breastfed group. Ezechi et al 2 noted that majority of the HIV positive women opted not to breastfeed after counseling on infant feeding options in context of HIV infection.…”
Section: Resultsmentioning
confidence: 89%
“…Ongoing studies are evaluating this question. 35 In addition, there is differential penetration of ARV drugs into human milk. Some ARVs have concentrations in human milk that are much higher than concentrations in maternal plasma, and others have human milk concentrations that are much lower than in plasma or are not detectable.…”
Section: Avoidance Of Hiv-1 Infection From Human Milkmentioning
confidence: 99%